Pengaruh Cash Ratio, Return On Investment, Return On Equity, terhadap Devidend Payout Ratio pada Perusahaan Manufaktur di Bursa Efek Indonesia - Suwetja, I Gede (Universitas Sam Ratulangi, 2014)
The main factor that affecting the investors to invest is the expected return in form of capital gain and dividend. To determine the amount of dividends to distribute for shareholders is very difficult. It is because the amount of dividends often related with firm value, revenue estimate, and future performance of firms. The objective of this study is to find the effect of cash ratio, return on investment and return on equity to dividend payout ratio, by conducting multiple regression method with samples taken by purposive sampling method. The data of this study is using financial statements of manufacturer companies in period of 2007 till 2010 and published by Indonesia Stock Exchange. The results of this study is showing there are significant effect of cash ratio, return on investment and return on equity to dividend payout ratio simultaneously. And partially, there is only return on investment.